2014
DOI: 10.1016/j.geothermics.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on optimized stimulation of intact and naturally fractured deep geothermal reservoirs using hydro-mechanical coupled discrete particles joints model

Abstract: This numerical study investigates hydraulic fracturing and induced seismicity in intact and fractured reservoirs under anisotropic in situ stress using hydro-mechanical coupled discrete particles joints model. A 2 km 2 km reservoir model with granitic rock and joints properties is constructed. Various injection scenarios are tested which involve continuous and cyclic styles of pressure controlled and flow rate controlled injections. Results are compared which include: spatial and temporal evolution of induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 35 publications
0
76
0
Order By: Relevance
“…Due to poroelastic effects, it is impossible to distinguish between the two types of anisotropy from geothermal seismicity alone. In addition, Yoon et al (2014) using hydromechanical coupled discrete fracture network models demonstrated that also the injection scenario affects the shape of the seismic cloud. A clear understanding of the physical processes operating at the border between seismically inactive and seismically active zones (asperity, hydraulic barrier) needs to be developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to poroelastic effects, it is impossible to distinguish between the two types of anisotropy from geothermal seismicity alone. In addition, Yoon et al (2014) using hydromechanical coupled discrete fracture network models demonstrated that also the injection scenario affects the shape of the seismic cloud. A clear understanding of the physical processes operating at the border between seismically inactive and seismically active zones (asperity, hydraulic barrier) needs to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…A dynamic fracture-growth approach is the discrete fracture network model by Yoon et al (2014) (see Fig. 8).…”
Section: Maximum Observed and Expected Seismic Magnitudementioning
confidence: 99%
See 1 more Smart Citation
“…Dissimilar to recent studies by Zang et al (2013) and Yoon et al (2014Yoon et al ( , 2015aYoon et al ( , 2015b, the model investigated in this study contains a large fault zone. Not only the seismic events computed from bond breakages, but also the seismic events by fracture slip are taken into account and compared with field observations.…”
Section: Introductionmentioning
confidence: 83%
“…Flow of viscous fluid in a bonded particle assembly is modeled and fluid volume and pressure driven breakages of bonds in mode I and mode II are simulated Zang et al 2013;Yoon et al 2014). Fluid flow is simulated by assuming that each bonded contact is a flow channel (Fig.…”
Section: Hydromechanical-coupled Dynamic Discrete Element Modelmentioning
confidence: 99%